The Antecedent: The Role Of Earnings Management In A Manufacturing Company - M Firza alpi; Nasrul Kahfi Lubis; Puja Rizqy Ramadhan (International Journal Reglement & Society (IJRS), 2022)
This study aims to examine and analyze the effect of tax planning, Net Profit Margin and deferred tax assets on earnings management in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017 - 2019 period. The population used in this study were 51 manufacturing companies. listed on the Indonesia Stock Exchange, while the samples taken were 13 manufacturing companies using purposive sampling. The independent variable used in this research is Earnings Management and the dependent variable is Tax Planning, Net Profit Margin and Deferred Tax Assets. This study uses an associative approach. The type of data in this research is quantitative. The data analysis technique in this research is using Descriptive Statistical Analysis, Simple Linear Regression analysis, classical assumption test, hypothesis test, and Coefficient of Determination. The results of this study indicate that tax planning has a positive and significant effect on earnings management. Net Profit Margin has a positive and insignificant effect on earnings management. Deferred tax assets have a negative and significant effect on earnings management. Tax planning, Net Profit Margin, Deferred Tax Assets have a significant effect on earnings management together